PRE-DESIGN OF COMMON BEAN CULTIVATION SYSTEM (PHASEOLUS VULGARIS VAR. TRESNA) INTEGRATED WITH ORGANIC WASTE PROCESSING BY BLACK SOLDIER FLY (HERMETIA ILLUCENS) - Selvia, Nola
Common beans are a horticultural crop that can be categorized as a functional food source of vegetable protein and vitamins. In addition, beans also contain various organic compounds that can help prevent chronic diseases in the body. Beans are quite popular among Indonesians and are usually consumed by processing them into various dishes. This makes the demand for beans stable and continues to increase every year. In fact, beans have long been cultivated as an export commodity in West Bandung Regency and have a much higher selling price than the local market. Therefore, beans farming is very promising to do because it has a fast cultivation time that reduces the risk of failure and profits are obtained more quickly. Currently, bean production still relies heavily on chemical fertilizers and pesticides which, if used excessively and continuously, will have a negative impact on the environment. One of the efforts that can be made to reduce the use of chemicals in agriculture is to replace chemical fertilizers with organic fertilizers. In the research of the final task 1 that has been carried out. It is known that kasgot organic fertilizer has a high content of macro elements ranging from 3-5% and minerals. The application of compost fertilizer can be done by mixing directly into the soil or used as an ingredient in making compost tea which has an excess of microorganism content. The need for kasgot fertilizer will be met by the establishment of a BSF cultivation unit that bioconverts kitchen and agricultural waste to produce kasgot fertilizer and saleable prepupae. Therefore, a biomass production system was selected based on the evaluation of the results of the final project 1, namely bean cultivation with compost tea integrated with BSF cultivation and waste treatment. This pre-design is a scale up from the previous research pilot scale of 100m2 to a full scale of 2500m2 (2000m2 bean field and 500m2 BSF field). The pre-design consists of two main subsystems, namely the BSF cultivation subsystem and the bean cultivation subsystem. The BSF cultivation subsystem is further divided into 7 units: egg hatching unit, rearing unit, maturation unit, breeding unit, compost drying unit, and compost tea making unit. The products produced from this subsystem are BSF dried prepupae and BSF leachate liquid organic fertilizer (POC). Meanwhile, the bean cultivation subsystem is divided into 2 units, namely the land preparation unit and the land cultivation unit. This subsystem produces fresh bean pods every harvest. Bean cultivation is carried out for 70 days per period until the plants die. The cultivation land is processed by forming beds that are 9m long, 1m wide, the planting distance is 50 x 50 cm, and the distance between beds is 40cm. The land was planted with the plotting method into two plots, the initial planting was carried out in the 2nd and 3rd weeks of January, and the next period in two weeks after the previous planting period ended. The cultivation area is 50 x 40 m, the BSF cultivation cage area is 30 x 10 m, the waste extraction and treatment unit area is 10 x 10 m, and the product storage room is 10 x 10 m. The business location is projected to be in Cairo. The business location is projected to be in Cigugur Girang, Parongpong Sub-district, West Bandung Regency, West Java. The business location is at coordinates -6o 83' 08283" S and 107o 58' 93316" E with an altitude of 1146 meters above sea level. The initial investment cost required to run the production process of a bean cultivation system integrated with BSF cultivation and waste treatment is Rp176,919,507.50. Revenue from the sale of beans with a production capacity of 7,199.64 kg/year is Rp103,674,816 per year, sale of BSF dry prepupa with a production capacity of 1446,69 kg/year is Rp80,725,089.76/year, and sale of leachate with a production capacity of 3,056.25 L/year is Rp68,765,625 /year. This business will receive profits when the Break Event Point (BEP) of the three products is reached, namely the BEP unit of beans of 5190.72 kg, prepupa of 654.10kg and leachate of 1397.03 liters so that the Multiproduct BEP is 7241.85 units. While the rupiah BEP for common beans is Rp83,051,591, for prepupa is Rp40,554,370, and for leachate is Rp34,925,682. Investment costs will be returned based on the calculation of the Payback Period in a period of 2 years 2 months and 6 days. During the first 5-year period, the NPV value of the business under normal conditions with an interest rate of 6% was obtained at Rp149,130,493.07 and the Net B/C Ratio was 1.17. The Internal Rate of Return (IRR) of this system is 34,57%. Based on the analysis that has been done, it can be concluded that the pre-designed integrated bean cultivation system with Black Soldier Fly cultivation and waste treatment is feasible.